2013
DOI: 10.1111/1440-1681.12099
|View full text |Cite
|
Sign up to set email alerts
|

Brain and retinal microglia in health and disease: An unrecognized target of the renin–angiotensin system

Abstract: Summary Microglia are the resident immune cells within the brain and retina, commonly known as the macrophages of the central nervous system (CNS). Microglia survey the surrounding milieu to eliminate invading microbes, clear cellular debris and enforce programmed cell death by removing apoptotic cells. Complementary to their ‘house‐keeping’ role, microglia are capable of releasing brain‐derived neurotrophic factor (BDNF), as well as various anti‐inflammatory cytokines that sustain and support neuronal survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 84 publications
0
32
0
Order By: Relevance
“…We have previously shown that IL-10 co-localizes with neurons after ischemic stroke (Fouda et al, 2013). Moreover, C21 is speculated to stimulate an IL-10 producing, anti-inflammatory microglia phenotype (McCarthy et al, 2013). C21 may also increase IL-10 production from systemic immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that IL-10 co-localizes with neurons after ischemic stroke (Fouda et al, 2013). Moreover, C21 is speculated to stimulate an IL-10 producing, anti-inflammatory microglia phenotype (McCarthy et al, 2013). C21 may also increase IL-10 production from systemic immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Functions of the glial cells are, among others, to supply and support the structure and architecture of the whole system, to enable and facilitate the nourishment of the neurons, to help building up the system, to keep the system functioning by removing cell debris, and to play an immunologic role. 2,9 In general, the neuroglial cells are smaller than the neural cells, but outnumber them by a factor of 5 to 10. 10 The ratio of glial cell number to neural cell number is highest in the basal ganglia, diencephalon, and brainstem (ratio > 10), followed by the cerebral cortex (ratio: 3 to 4), and it is relatively low in the cerebellum (ratio: 0.1 to 0.3).…”
Section: Microgliamentioning
confidence: 99%
“…Among other properties, they have the potential to release various factors that directly and/or indirectly promote regeneration in the injured nervous system. [1][2][3][4] It was the purpose of this review to elucidate the importance of the retinal microglial cells in the course, but not as the cause, of glaucomatous optic neuropathy, and to illustrate the role retinal microglial cells take in the interval between the primary damage set to the retinal ganglion cell axons, and the final death and disappearance of the ganglion cell axons and cell bodies. As the reaction of the microglial cells to a damaged retinal ganglion cell may not markedly depend on the primary causative mechanism, the features of the retinal microglial cells as described below with respect to glaucomatous optic neuropathy may also hold true for nonglaucomatous optic nerve damage such as in diabetic retinopathy or anterior ischemic optic neuropathy.…”
mentioning
confidence: 99%
“…36 Microglia have also been implicated in vascular development and in the maintenance of neuronal integrity in the central nervous system. 36,37 Moreover, release of proinflammatory cytokines from microglia is thought to contribute to the development of vascular pathology in OIR. 38 We examined whether microglia were altered in OIR or by valsartan treatment (Fig.…”
Section: Valsartan Restores the Number And Morphology Of Microglia Inmentioning
confidence: 99%
“…These findings are consistent with the emerging role of the RAS in the activation status of microglia in both the brain and retina. 37 …”
Section: Valsartan Reduces Pathological Neovascularization and The MImentioning
confidence: 99%